ANALYSIS OF THE USE OF ANTIBIOTICS IN ASYMPTOMATIC, MILD, AND MODERATE COVID-19 PATIENTS TREATED IN BHAYANGKARA HOSPITAL - Putri Ayu Irma Ikasanti; Rika Yulia; Fauna Herawati; Ruddy Hartono; Puri Safitri Hanum (Jurnal Berkala Epidemiologi, 2022)
Background: COVID-19 is an infectious disease caused by a new type of virus named SARS-CoV-2. There is still no specific treatment for COVID-19; the antibiotic is used for therapy and to prevent severe disease, so the increasing use of antibiotics in COVID-19 patients will lead to a detrimental impact and the risk of antibiotic resistance. Purpose: This study aims to analyze antibiotic use frequency and determine the number of DDD per 100 bed-days in July – December 2020 at Bhayangkara Hospital Surabaya. Methods: This research was a descriptive study with a retrospective study design conducted at Bhayangkara Hospital Surabaya in May – June 2021. The data were collected from 94 medical records, inclusion criteria: all ages; asymptomatic, mild, and moderate categories; all hospitalized patients in July-December 2020 who received antibiotics; the exclusion criteria: non-confirmed COVID-19 patients who had comorbidities and received antibiotics; the patient who died. The variables: frequency of antibiotic use with calculating the number of DDD/100 bed-days and percentage of COVID-19 patients who received antibiotics during hospitalization. Results: The frequency of antibiotic use in asymptomatic, mild, and moderate COVID-19 patients: 86.56 DDD/100 bed-days, the most antibiotic use was azithromycin at 50.42 DDD/100 bed-days and Levofloxacin at 22.70 DDD/100 bed-days. All asymptomatic, mild, and moderate COVID-19 patients (100%) at Bhayangkara Hospital Surabaya were treated with antibiotics, whereas the condition of patients was 5.32% asymptomatic, 48.94% mild, and 45.74% moderate. Conclusion: There is overuse of antibiotics in asymptomatic, mild and moderate COVID-19 patients at Bhayangkara Hospital Surabaya.